2020
DOI: 10.1016/j.arrct.2020.100052
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned: The Difficulties of Incorporating Intensity Principles Into Inpatient Stroke Rehabilitation

Abstract: Objective The objective of this study was to determine the feasibility of a rehabilitation approach focusing on cardiovascular, strength, and gait training intensity in the inpatient rehabilitation setting after a new onset of stroke. We additionally aimed to determine the efficacy of this intensity-based program on rehabilitation outcomes compared with usual care. Design Participants were pseudo-randomized to an intensity-based program focusing on gait, cardiovascular,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Remarkably, the vast majority of the patients had already received intensive rehabilitation previously. Previous research showed small differences in ADL abilities only for longer time in rehabilitation with higher therapy intensity [ 19 , 20 ]. The median therapy intensity at P.A.N.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the vast majority of the patients had already received intensive rehabilitation previously. Previous research showed small differences in ADL abilities only for longer time in rehabilitation with higher therapy intensity [ 19 , 20 ]. The median therapy intensity at P.A.N.…”
Section: Discussionmentioning
confidence: 99%
“…There is still work to be done related to translating research into practice and decreasing the research-to-practice gap in the rehabilitation settings despite many efforts being made by many teams (26,28). The shorter time it takes for the latest evidence to be applied to clinical practice, the greater chance for patients to receive better care (39).…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple examples of pragmatic research projects that use the KTA and the CFIR in a rehabilitation setting. Studies suggest that using the CFIR may increase the replicability and generalizability of study findings (26)(27)(28), and the KTA cycle can contribute to positive changes in stroke rehabilitation practices (21).…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to performing HIT during routine inpatient rehabilitation post-stroke are multifactorial and may include minimal didactic education and training on psychomotor skills used to provide HIT in lower functioning individuals, lack of heart rate monitoring and gait training equipment, patient safety concerns, and the extent of many patients' physical deficits. 14,15 However, previous studies have shown that such implementation is feasible. 1,16 In particular, a cohort study of 201 individuals post-stroke receiving HIT focused on stepping during inpatient rehabilitation performed approximately 1500 steps/day, with substantial gains in locomotor function as well as balance and transfers despite reduced attention towards these latter tasks.…”
Section: Introductionmentioning
confidence: 99%